Chemoinformatics approaches to virtual screening - Varnek, Alexandre; Tropsha, Alex (RSC Pub., 2008)
Focuses on chemoinformatics approaches applicable to virtual screening of very large available collections of chemical compounds to identify novel biologically active molecules.